2020
DOI: 10.1073/pnas.2009074117
|View full text |Cite
|
Sign up to set email alerts
|

A field-based quantitative analysis of sublethal effects of air pollution on pollinators

Abstract: While the impact of air pollution on human health is well studied, mechanistic impacts of air pollution on wild systems, including those providing essential ecosystem services, are largely unknown, but directly impact our health and well-being. India is the world’s largest fruit producer, second most populous country, and contains 9 of the world’s 10 most polluted cities. Here, we sampled Giant Asian honey bees, Apis dorsata, at locations with varying air pollution levels in Bangalore, India. We observed signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 56 publications
2
49
2
Order By: Relevance
“…In a recent study conducted in India where there are many of the world most polluted cities, significant correlations between PM10 increases and physiological changes of Giant Asian honeybees ( Apis dorsata ) were found (Thimmegowda et al., 2020). Giant Asian honeybee samples from severely polluted areas (in Bangalore, India) showed significantly lower rates of survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study conducted in India where there are many of the world most polluted cities, significant correlations between PM10 increases and physiological changes of Giant Asian honeybees ( Apis dorsata ) were found (Thimmegowda et al., 2020). Giant Asian honeybee samples from severely polluted areas (in Bangalore, India) showed significantly lower rates of survival.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, colony‐level chronic impacts through gene expression could also be predicted. For example, vitellogenin, associated with survival of worker bees, was found depleted in bees sampled from the highly polluted site compared with those from the low polluted site (Thimmegowda et al., 2020). This is important because the reduced fitness of individual foragers and their colony due to degraded foraging performance may have detrimental impacts on pollination services.…”
Section: Discussionmentioning
confidence: 99%
“…Honeybees have been used as biomonitors of air pollutants, and a limited number of studies have examined pollutant effects on olfactory learning and memory [ 155 ]. Effects on social behavior from air pollutants have yet to be investigated, however a recent study found an association between particulate matter air pollution and flower visitation, expression of stress-related genes, and survival in the Giant Asian honeybee, Apis dorsata [ 156 ]. Given the ability to track and monitor individual interactions at high spatial and temporal resolution [ 157 ], honeybees could become a powerful model system to examine effects of air pollution.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, CYP9E2 has been shown to metabolize thiacloprid efficiently in honeybees, whereas other CYPs cannot fulfil this function 73 . Moreover, a recent analysis of the sublethal effects of air pollution, a chemically complex stressor, also showed that cyp9e2 was strongly upregulated in honeybee heart tissue 74 . Our data indicate that biotic and abiotic stressors induce the preferred expression of genes encoding UGTs and catalase, respectively, whereas CYP9E2 appears to fulfil a universal detoxification function.…”
Section: Discussionmentioning
confidence: 98%